Polimorfismos dos genes SLC11A1 e DLA-DRB1 e susceptibilidade de cães à leishmaniose - Ribeiro, Érica de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The importance of visceral leishmaniasis in the context of public health has increased in the last decade. The manifestation of visceral leishmaniasis in dogs is variable and genetic studies and its relationship with visceral leishmaniasis have shown some candidate genes involved in susceptibility and resistance to this disease. This study aimed at evaluating the relationship between polymorphism of the genes Slc11a (solute carrier family 11 member 1), and DLA-DRB1 (dog leukocyte antigen) and the positivity to leishmaniasis determined by the amplification of Leishmania sp. kinetoplast DNA by PCR and the presence of anti-Leishmania sp. the indirect ELISA. We observed statistically significant associations between the leishmaniasis positive diagnosis and i. the presence of intron 1 microsatellite region alleles (141, 145 or 149) (P<0.0001), ii. the variation on the guanine number (8 or 9) in the promoter region (P=0.0280) (in both cases when analyzed separately), iii. the presence any of the microsatellite alleles associated to 8 or 9 G in the promoter region (P=0.0025). Microsatellite allele 141 was associated to negativity to leishmaniasis (P<0.0001). There was no association between the presence of any of the exon 2 DLA-DRB1 alleles and the leishmaniasis positive animals, although significant association between the frequency of the alleles DRB1-W, DRB1*00101 or DRB1-T and negative results to leishmaniasis were observed. These might be potential markers for dog’s resistance to visceral leishmaniasis

A importância da leishmaniose visceral no contexto da saúde pública tem aumentado na ultima década. A manifestação da leishmaniose visceral nos cães é variável e estudos sobre a genética e a sua relação com a leishmaniose visceral têm indicado alguns genes envolvidos na susceptibilidade e resistência a esta doença. O objetivo deste estudo foi avaliar a relação entre as variantes alélicas dos gene Slc11a1 (solute carrier family 11 member 1) e DLA-DRB1 (dog leukocyte antigen) com a positividade para leishmaniose, determinada por meio da amplificação de DNA de cinetoplasto de Leishmania sp., por PCR, e pela presença de anticorpos anti-Leishmania sp. ao teste ELISA indireto. Foram observadas associações estatisticamente significantes entre a positividade para leishmaniose e: i. a presença do alelo (141, 145 ou 149) da região microssatélite (TAAA)n localizada no íntron 1 do gene Slc11a1 (P< 0,0001) ii. a variação do número de guaninas (8 ou 9 G) da região promotora (P=0,0280) (em ambos os casos quando analisados separadamente) e iii. a presença de qualquer dos alelos da região microssatélite associado a 8 ou 9 G da região promotora (P= 0,0025). A presença do alelo 141 foi estatisticamente associada à negatividade em cães (P<0,0001). Não foi observada associação estatisticamente significante entre a positividade à leishmaniose e a freqüência dos alelos do exon 2 do gene DLA- DRB1, embora tenha sido observada associação significante entre a freqüência dos alelos DRB1-W, DRB1*00101 ou DRB1-T e o resultado negativo para leishmaniose, podendo ser estes potenciais marcadores para resistência à leishmaniose em cães
Keywords: Leishmaniose visceral; Reação em cadeia de polimerase; Polymerase chain reaction; Visceral leishmaniasis